Evaluation of recombinant botulinum neurotoxin type A1 efficacy in peripheral inflammatory pain in mice - Oehler, Beatrice; Périer, Cindy; Martin, Vincent; Fisher, Amy; Lezmi, Stéphane; Kalinichev, Mikhail; McMahon, Stephen B. (Frontiers in molecular neuroscience, 2022)
Well-established efficacy of botulinum neurotoxin type A (BoNT/A) in aesthetic dermatology and neuromuscular hyperactivity disorders relies on canonical interruption of acetylcholine neurotransmission at the neuromuscular junction at the site of the injection. The mechanisms and the site of activity of BoNT/A in pain, on the other hand, remain elusive. Here, we explored analgesic activity of recombinant BoNT/A1 (rBoNT/A1; IPN10260) in a mouse model of inflammatory pain to investigate the potential role of peripheral sensory afferents in this activity. After confirming analgesic efficacy of rBoNT/A1 on CFA-induced mechanical hypersensitivity in C57Bl6J mice, we used GCaMP6s to perform in vivo calcium imaging in the ipsilateral dorsal root ganglion (DRG) neurons in rBoNT/A1 vs. vehicle-treated mice at baseline and following administration of a range of mechanical and thermal stimuli. Additionally, immunohisochemical studies were performed to detect cleaved SNAP25 in the skin, DRGs and the spinal cord. Injection of CFA resulted in reduced mechanical sensitivity threshold and increased calcium fluctuations in the DRG neurons. While rBoNT/A1 reduced mechanical hypersensitivity, calcium fluctuations in the DRG of rBoNT/A1- and vehicle-treated animals were similar. Cleaved SNAP25 was largely absent in the skin and the DRG but present in the lumbar spinal cord of rBoNT/A1-treated animals. Taken together, rBoNT/A1 ameliorates mechanical hypersensitivity related to inflammation, while the signal transmission from the peripheral sensory afferents to the DRG remained unchanged. This strengthens the possibility that spinal, rather than peripheral, mechanisms play a role in the mediation of analgesic efficacy of BoNT/A in inflammatory pain.
Gesehen am 15.07.2022